The Waterfall Model in the Implementation of a Room Reservation Information System: A Case Study at a University - Setiawan, Akas Bagus; Rizaldi, Taufiq (Journal of Information Technology and Cyber Security, 2024)
Politeknik Negeri Jember (National State of Jember Polytechnic), Indonesia, fully understand that infrastructure is one among various key factors to enhance the quality of the university. However, in the department of Information Technology, infrastructure management is a prominent issue. The primary cause of the issue appears to be a manual arrangement of room reservations, as room usage often crashes due to the scheduling mismatch. To tackle this issue, this study focuses on the development of a room reservation information system, known as “Sistem Informasi Peminjaman Ruangan dan Sarana Pembelajaran (SIPRu)”. The system is developed as an additional feature in the department website. It is developed using the Waterfall method, beginning with the requirements analysis (i.e., an identification of functional and non-functional requirements) and architectural processes design processes (i.e., the development of use case diagram, flowchart, data flow diagram, and database design). In this study, Laravel is used for the implementation, and black box testing is used to verify compliance with the functional requirements. During the testing process, 42 department stakeholders participated to validate the requirements and conduct user experience testing. The results indicated that the stakeholders have found the website to be sufficiently responsive to their needs. Furthermore, it is revealed that SIPRu is effective at assisting users in reserving rooms at the department of Information Technology, National State of Jember Polytechnic.